Production performance of nursery graded eel Anguilla bicolor bicolor in recirculating aquaculture system - Budiardi, Tatag; Effendi, Irzal; Rahman, Muhammad Aghistni; Vinasyiam, Apriana (Jurnal Akuakultur Indonesia, 2022)
The growth rate highly varies in nurseries of eel. Variations in size lead to competition in obtaining feed, this causes stunting of smaller fish. This situation leads to high production costs due to poor feed utilization efficiency. Grading needs to be done periodically to improve nursery production performance. Water quality is controlled by a recirculation system that can support production performance through the degradation of toxic compounds. This study aims to analyze the production and nursery performance of graded eel (Anguilla bicolor bicolor) that graded in the same batch in a recirculation system. Completely randomized design (CRD) consisting of three treatments with four replications was used in this research. The treatments included nursery of graded eels for 60 days in three groups of initial weight size, namely 0,35±0,00 g (A); 0,50±0,00 g (B); and 1,04±0,00 g (C). There were 344 eels (A), 239 eels (B), and 116 eels (C) in each replication. The best nursery production performance was obtained in the treatment of 1,04±0,00 g, and the best nursery business performance was obtained in the treatment of 0,50±0,00 g.